Development of a UWB-Based Trilateration System for Multi-Mobile Node Indoor Localization - Hary Oktavianto; Haniif Mulya Wicaksana; Audra Annisa Zhafirah; Mohammad Syafrudin; Prima Kristalina; Bambang Sumantri (Journal of Electrical and Intelligent Systems, 2026)
Accurate indoor localization is essential for navigation and coordination in multi-agent systems, particularly in environments where Global Positioning System (GPS) signals are unavailable. While ultrawideband (UWB)-based trilateration has been widely studied, most existing works focus on single-node localization and do not explicitly address scalability in terms of computational cost and processing time. This study proposes a scalable multi-mobile node localization framework based on UWB trilateration, with a key contribution in demonstrating linear computational growth with respect to the number of mobile nodes. The system employs UWB DWM1000 modules and the Symmetrical Double-Sided Two-Way Ranging (SDS-TWR) method to estimate distances between mobile nodes and anchor nodes, followed by onboard trilateration for position estimation. Experimental validation is conducted using up to four simultaneous mobile nodes within a 10×10 m indoor environment. The results show that the proposed system maintains centimeter-level accuracy, with RMSE values of 10.08 cm, 11.46 cm, 12.25 cm, and 9.13 cm for nodes 1 to 4, respectively. More importantly, the processing time increases consistently from 55 ms (one node) to 115 ms (four nodes), exhibiting an approximately constant incremental cost of 20 ms per additional node, which confirms the linear scalability of the proposed approach. These findings highlight that the proposed system not only achieves reliable localization accuracy but also ensures predictable and efficient computational performance, making it suitable for real-time multi-node applications such as robot swarm coordination and collaborative autonomous systems.